1994
DOI: 10.1523/jneurosci.14-06-03934.1994
|View full text |Cite
|
Sign up to set email alerts
|

Immunolocalization of calpain I-mediated spectrin degradation to vulnerable neurons in the ischemic gerbil brain

Abstract: Transient ischemia-induced perturbations in calcium homeostasis have been proposed to lead to pathological activation of the cysteine protease calpain I and subsequent delayed neuronal death in the CA1 region of hippocampus. We report here on the design and characterization of antibodies selective for calpain-generated fragments of brain spectrin, and their use for immunoblot and immunohistochemical analyses of calpain activation following cerebral ischemia in the gerbil. Although spectrin was susceptible to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
265
0

Year Published

1995
1995
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 315 publications
(283 citation statements)
references
References 50 publications
18
265
0
Order By: Relevance
“…An increase of the SBDP15O content has been reported in vivo in models for excitotoxicity (Vartanian et a!., 1996), focal ischemia , and global ischemia (Roberts-Lewis et al, 1994) and in cell cultures subjected to excitotoxins ( Siman and Noszek, 1988) and OGD (Wang et a!., 1996a,b). However, those reports preceded the recent discovery that a-spectrin is a substrate for caspases (Nath et a!., 1996a;Cryns et a!., 1996;Vanags et al, 1996).…”
Section: Discussionmentioning
confidence: 88%
“…An increase of the SBDP15O content has been reported in vivo in models for excitotoxicity (Vartanian et a!., 1996), focal ischemia , and global ischemia (Roberts-Lewis et al, 1994) and in cell cultures subjected to excitotoxins ( Siman and Noszek, 1988) and OGD (Wang et a!., 1996a,b). However, those reports preceded the recent discovery that a-spectrin is a substrate for caspases (Nath et a!., 1996a;Cryns et a!., 1996;Vanags et al, 1996).…”
Section: Discussionmentioning
confidence: 88%
“…Excessive glutamate receptor activation has also been hypothesized to contribute to spectrin breakdown. Glutamate receptor agonists, as well as ischemic and traumatic brain injury, result in the activation of calpain I and the breakdown of spectrin into calpain Jcleaved fragments (Siman and Noszek, 1988;Siman et al, 1989;Roberts-Lewis et al, 1994;Kampfl et al, 1 996a,b). Finally, several studies have demonstrated that treatments with protease inhibitors that block calpain activity will inhibit MAP2 and spectrmn degradation and will promote neuron survival after excitatory or traumatic CNS injury (Arai et al, 1990;Arlinghaus et al, 1991;Lee et al, 1991;Caner et al, 1993;Rami and Kriegistein, 1993;Bartus et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…This contributes to the dendritic remodeling, interruption of membrane and cytoplasmic transportation, modulation of gene expression, and neuronal degeneration (Wang et al, 1990;Faddis et al, 1997;Wang, 2000). The activation of calpain I has been reported, following the activation of ionotropic glutamate receptors or hypoxic-ischemic insults (Seubert et al, 1988;Ostwald et al, 1993;Roberts-Lewis et al, 1994). Selective inhibitors of calpain I can reduce the NMDA-, kainate-, or AMPA-mediated excitotoxicity to some extent, and attenuate brain damage after hypoxia, focal cerebral ischemia, or transient global cerebral ischemia (Lee et al, 1991;Rami and Krieglstein, 1993;Hong et al, 1994).…”
Section: Excitotoxicitymentioning
confidence: 99%